STUDI TENTANG PERANAN PROGRAM EKSTRAKURIKULER PUSAT INFORMASI DAN KONSELING REMAJA (PIK-R) DALAM MENANAMKAN KARAKTER RASA INGIN TAHU SISWA DI SMP NEGERI 7 PEKANBARU - Suci Fadilla Harianti H; Ahmad Eddison; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Extracurricular information centers and youth counseling (PIK-R)have a very important role in the lives of adolescents. Where its role is to make youngpeople who can do advocacy and IEC, build youth-friendly PIK-R, communicateinformation and education in schools and the community environment. Then it isnecessary to instill character education, especially the character of curiosity. With thiscuriosity character, siswa can anticipate the influence of the school environment andlcommunity environment. The purpose of this study was to determine how the role ofinformation center and youth counseling extracurricular programs (PIK-R) in instillingthe character of curiosity of studentswa in SMP Negeri 7 Pekanbaru. To find out howthe character of students' curiosity in SMP Negeri 7 Pekanbaru. To find out how toinfluencethe role of information center and youth counseling extracurricular programs(PIK-R) in instilling the character of curiosity siswa in SMP Negeri 7 Pekanbaru. Thepopulation in this study were students who participated in the extracurricularinformation center and youth counseling (PIK-R) of 38 students. The sample in thisstudy were all students who took the extracurricular information center and youthcounseling (PIK-R). Data collection techniques were carried out using the method ofobservation, questionnaires, interviews and documentation. The results showedthe roleof information center and youth counseling extracurricular programs (PIK-R) ininstilling the character of curiosity siswa at SMP Negeri 7 Pekanbaru at a very goodlevel. There is a significant influence in this study, it is known that the results of asimple linear regression test between variables X and Y, obtained Fcount of 15,129 andFtable of 4.11 shows Fcount> Ftable, so that Ho is rejected and Ha is accepted. Theinfluence is moderate because of 54.4%.Key Words: Role, PIK-R, Character of Curiosity